European Parliament election study 1999 - Holmberg, Sören; Statistics Sweden (University of Gothenburg, 2014)
The second Swedish election to the EU-parliament was held on the 13th of June 1999. As in connection to all general elections and referenda held in Sweden since 1956, an election study was carried out in connection to this election. The main subject of the survey was the European Union and the respondent´s attitudes toward the Swedish EU membership, but the survey also included a number of questions asked in one or several of the Swedish election studies.
General questions about politics included: daily newspaper reading habits regarding national politics, local politics, politics in foreign countries and EU-related issues; exposure to news in different media; interest in politics in general, as well as in EU-related issues; the importance of the EU-parliament election and if any issues were of particular importance when deciding how to vote in the election; opinion on the most positive and the most negative effects of EU; opinion on the political parties and their party leaders on a scale ranging from -5 to +5; trust in Swedish politicians, the EU-parliament, the EU-commission, and in the Swedish parliament; opinion on the social democratic government; the most important issues to deal with within the European Union; party preferences; placement of respondent and the political parties on a political left-right scale. Furthermore the respondents had to state their opinion on a number of currently debated issues. Respondents had to give their opinion on the effect of a Swedish EU-membership on areas such as: environment, economy, employment, agriculture, social security, equality between men and women, military security, national independence, development of the European Union, price level of food, crime prevention, immigrants and refugees. They also had to give their judgement of the achievment of the European Union within the same areas, and if they prefered decisions in these areas to be taken on national or European Union level. The respondents had to give their opinion on a number of EU-related issues such as: a Swedish withdrawal from the European Union, Swedish EMU-membership, enlargement of the EU, Swedish participation in the EU defence cooperation, reduction of the possibilities for the member countries to put one´s veto, reintroduction of harder border control between EU member countries, reduction of the support to farmers within the EU, and decriminalization of the usage of hashish. For each of the following countries: the Baltic states, Cyprus, the Czech Republic, Hungary, Poland, Romania, Turkey, Russia, Ukraine, and Morocco, the respondents had to state if and how soon they should become members of the EU. Respondents had to give their own opinion on: the Swedish EU-membership, as well as their view of political parties for and against a Swedish membership; Sweden´s relation to the European Union in the future; a development of EU towards a federation. Regarding a Swedish membership of the European Monetary Union, respondents had to place the political parties as well as themselves on a ten degree scale according to how positive or negative they were towards the EMU. Respondents had to state how satisfied they were with the way democracy works within Sweden and the European Union respectively, and how proud they are to be Swedish. A number of questions dealt with the election to the EU-parliament such as participation; issues important for the decision how to vote; when the respondent decided how to vote; most important reason to vote; knowledge of candidates; opinion on the different candidates; and exposure to the election campaign. Nonvoters were asked about the reason not to vote, and voters were asked if they used the possibility to vote for a specific person. Demographic item include gender, age, marital status, children, education and occupation.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Det andra svenska valet till EU-parlamentet hölls den 13 juni 1999. Liksom vid alla allmänna val och folkomröstningar hållna i Sverige sedan 1956 genomfördes en valundersökning i samband med detta val. Det huvudsakliga ämnet för undersökningen var Europeiska unionen och respondenternas inställning till det svenska EU-medlemskapet, men undersökningen innehåller även ett antal frågor som ställts i en eller flera av de tidigare svenska valundersökningarna.

Bland de allmänna frågorna om politik ingick: läsvanor om nationell och lokal politik, politik i andra länder och EU-relaterade frågor, exponering för nyheter i olika medier, intresse för politik i allmänhet och för EU-relaterade frågor, EU-parlamentsvalets betydelse, och om det fanns frågor av särskild betydelse för beslutet hur man skulle rösta i valet, åsikt om de mest positiva och de mest negativa effekterna av EU, inställning till de politiska partierna och deras partiledare, förtroende för svenska politiker, EU-parlamentet, EU-kommissionen och den svenska riksdagen, inställning till den socialdemokratiska regeringen, de viktigaste frågorna att ta itu med inom Europeiska unionen, partipreferens; respondentens och de politiska partiernas placering på en politisk vänster-höger skala. Dessutom fick respondenterna yttra sig om ett antal aktuella frågor i den politiska debatten.
Respondenterna fick yttra sig om effekterna av ett svenskt EU-medlemskap på områden som: miljö, ekonomi, sysselsättning, jordbruk, social trygghet, jämställdhet mellan män och kvinnor, militär säkerhet, nationellt oberoende, utveckling av Europeiska unionen, prisnivå på mat, brottsförebyggande, invandrare och flyktingar. De fick också ge sin bedömning av vad den Europeiska unionen uppnått inom dessa områden, samt om man ansåg att beslut inom dessa områden borde tas på nationell eller EU-nivå.

Respondenterna fick yttra sig om ett antal EU-relaterade frågor såsom: ett svenskt utträde ur EU, svenskt EMU-medlemskap, EU: s utvidgning, svenskt deltagande i EU:s försvarssamarbete, minskning av medlemsländernas veto-möjligheter, återinförande av hårdare gränskontroller mellan EU:s medlemsländer, minskning av stöd till jordbrukare inom EU, och avkriminalisering av användningen av hasch. För vart och ett av följande länder: de baltiska staterna, Cypern, Tjeckien, Ungern, Polen, Rumänien, Turkiet, Ryssland, Ukraina och Marocko fick respondenterna ange om och hur snabbt de ska bli medlemmar i EU. Respondenterna fick ange sina egna synpunkter på: det svenska EU-medlemskapet, liksom deras syn på de politiska partiernas inställning till det svenska medlemskap, Sveriges framtida förhållande till EU, och en eventuell utveckling av EU mot en federation.

När det gäller ett svenskt medlemskap i den europeiska monetära unionen, skulle respondenterna placera de politiska partierna samt sig själva på en tio graders skala beroende på hur positiv eller negativ de var till EMU. Respondenterna fick ange hur nöjda de var med hur demokratin fungerar i Sverige och EU respektive, och hur stolta de är över att vara svenskar. Ett antal frågor behandlade valet till EU-parlamentet såsom deltagande, frågor viktiga för beslutet hur man skulle rösta, när den svarande beslutat hur man skulle rösta, viktigaste skälet att rösta, kunskap om kandidaterna, inställning till de olika kandidaterna; och exponering för valkampanjen. Icke-röstande tillfrågades om orsaken varför man inte röstat, och de som röstat tillfrågades om de använde möjligheten att personrösta. Demografiska bakgrundsuppgifter innefattar kön, ålder, civilstånd, barn, utbildning och yrke.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Europaparlamentsvalundersökning 1999
EUP99
Keywords: elections; val; european union; europeiska unionen; european integration; europeisk integration; election data; valdata; european parliament; europaparlamentet; single european currency; gemensam europeisk valuta; internal politics; inrikespolitik; election campaigns; valkampanjer; electoral issues; valfrågor; free will; fri vilja; european parliament elections; europaparlamentsval; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap